FUNGSI LINGKUNGAN TERBANGUN DI KORIDOR CIGONDEWAH SEBAGAI IDENTITAS KAWASAN INDUSTRI KREATIF DI KOTA BANDUNG - Wijaya, Karto; Wibowo, Heru (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2018)
This developing area provides a very wide potential in the development as an area that has excellent products or development projects in Bandung. Cigondewah area has the potential to become this area as a creative industrial area that can support the income of the people and the city of Bandung. Cigondewah is one of the areas known as the Cigondewah environment and surrounding areas as a creative industrial area about the utilization of textile industry waste that sells the rest of cloth from factories around the city of Bandung. The area of Cigondewah grows and develops with the uniqueness of the community itself that will take advantage of opportunities from the textile industry, homes along the road corridor that turns into the shelter, the community into warehouses and shops to sell fabrics.It is also the aim of the government to promote and develop tourist areas Cigondewah for the future to be better again to enhance the identity of the area Cigondewah as a tourist area fabric shopping in the city of Bandung. This study aims to determine the development of creative industries in Cigondewah. Cigondewah Textile Tourism Area of Bandung City, especially Capacity Building, to show the identity and image of Cigondewah area as a textile tourism area in Bandung City. The identity of Cigondewah area which is currently called Cigondewah as Tourism Shopping Area Cloth. From this research is expected to give an idea that the environment is in the corridor Cigondewah road.